2004
DOI: 10.1176/appi.ajp.161.6.1090
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Other Mental Health Diagnoses Increase Mortality Risk After Ischemic Stroke

Abstract: Despite being younger and having fewer chronic conditions, a higher 3-year mortality risk was seen in patients with poststroke depression and other mental health diagnoses after hospitalization for an ischemic stroke. The biological and psychosocial mechanisms driving this greater risk should be further explored, and the effect of depression treatment on mortality after stroke should be tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
170
0
19

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 272 publications
(198 citation statements)
references
References 43 publications
9
170
0
19
Order By: Relevance
“…PSD is associated with worse functional outcomes, quality of life, and increased post-stroke mortality. [6][7][8][9] Our prior work has demonstrated that these effects are present in veterans with PSD, as we found that those with a new depression diagnosis post-stroke had a 25% increase in mortality 9 and health care utilization 10 post-stroke.…”
Section: Introductionsupporting
confidence: 50%
“…PSD is associated with worse functional outcomes, quality of life, and increased post-stroke mortality. [6][7][8][9] Our prior work has demonstrated that these effects are present in veterans with PSD, as we found that those with a new depression diagnosis post-stroke had a 25% increase in mortality 9 and health care utilization 10 post-stroke.…”
Section: Introductionsupporting
confidence: 50%
“…Poststroke depression (PSD) has been recognized as a common sequela of stroke, with an increased morbidity and mortality (Williams, Ghose, & Swindle, 2004). PSD are approximately 85% of patients with strokes (Robinson & Jorge, 2016), and are associated with more serious functional dysfunction (Cully et al., 2005), delayed rehabilitation outcomes (Gillen, Tennen, McKee, Gernert‐Dott, & Affleck, 2001), as well as social withdrawal after stroke (Feibel & Springer, 1982; Robinson, Starr, Kubos, & Price, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a common complication after stroke and is associated with increased mortality [1], poor functional outcome [2], and decreased quality of life [3]. Over the past 20 years conflicting findings have been reported regarding the association between cognitive impairment and depressive pathology after stroke.…”
Section: Introductionmentioning
confidence: 99%